Boundary Shear Stress Analysis in Semi-Parabolic Channels - Siavash Heydari orojlo (علوم و مهندسی آبیاری, 2019)
Due to problems with on-site irrigation channels, such as occupying a high level of the land, a lack of suitable loan materials, and the possibility of dealing with multiple complications, the use of prefabricated channels is one of the most competitive options available for the  existing channels. From the theoretical point of view, the most effective hydraulic cross-section for the coated channels in which smooth water flows is the semicircular section. Nevertheless, in terms of implementation, the use of the semicircular cross-section is generally limited to the reinforced concrete channel. One of the important issues in outdoor hydraulic engineering is having sufficient knowledge about the amount of hydraulic resistance against the flow. The estimation of hydraulic resistance of the flow in open channels has always faced a serious challenge because of the presence of secondary currents and the vortex viscosity. The determination of the contribution of flow pipes in the bed and wall is faced with errors due to the effects of the walls on the maximum velocity position. Accurate prediction of boundary shear stress distributions in the open-channel flow is crucial in many engineering problems, such as channel design, the balance of energy, and sedimentation. Determining the exact bed and wall shear stress is important from a theoretic and applied point of view, for example, its role in scour and sedimentation studies and designing shield conservations.